Green preparation process using methyl lactate for cellulose-acetate-based nanofiltration membranes - Rasool, Muhammad Azam; Van Goethem, Cédric; Vankelecom, Ivo F.J. (Separation and purification technology, 2020)
[Display omitted] •Cellulose acetate (CA) membranes are successfully prepared using methyl lactate or 2-MeTHF as bio-based green solvents via phase inversion.•CA/methyl lactate systems had the potential to become tuned toward the membrane that was dense enough for nanofiltration.•Use of methyl lactate and 2-MeTHF are in agreement with principles of green chemistry. Cellulose acetate (CA) membranes were prepared via phase inversion using methyl lactate as a green solvent and 2-methyltetrahydrofuran as a green co-solvent with or without evaporation period prior to immersion of the cast polymer solution in the coagulation bath. The membrane morphologies were characterized using scanning electron microscopy and the membrane performance was screened using aqueous rose bengal (RB) or MgSO4 feed solutions. With CA-concentration in the casting solution increasing from 8 to 20 wt%, RB-rejection increased from 31.1% to 99.5%, while permeance decreased from 32.0 to 2.4 L/m2·h·bar. CA-membranes cast from a 10 wt% polymer solution had a RB-rejection higher than 92.0% with good permeance around 3.5 L/m2·h·bar at low co-solvent concentration (10 wt%). However, with increased co-solvent concentration (i.e. 30–50 wt%), both rejection and permeance surprisingly decreased, regardless evaporation time. For membranes cast from a 20 wt% polymer solution, RB-rejection remained around 99% and permeance decreased with increasing co-solvent concentration in the casting solution. MgSO4 rejection was around 93.0% for membranes cast from a 20 wt% polymer solution with 10 wt% co-solvent without evaporation (at a flux of 1.0 L/m2·h·bar) and 96.5% with evaporation at a flux of 1.3 L/m2·h·bar.